2018
DOI: 10.3892/etm.2018.6974
|View full text |Cite
|
Sign up to set email alerts
|

Role of modern imaging techniques for the in vivo diagnosis of lichen planus (Review)

Abstract: Lichen planus (LP) is a chronic inflammatory skin disease that can sometimes affect mucosal surfaces, with unknown pathogenesis, even though it appears to be an autoimmune disease. The diagnosis of lichen planus is usually based on histopathological examination of the lesions. Nowadays, the classical invasive diagnostic methods are replaced by modern non-invasive techniques. In this review, we present the main non-invasive imaging methods (dermoscopy, reflectance confocal microscopy, optical coherence tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 77 publications
0
35
0
Order By: Relevance
“…However, a study that focused on the immunogenicity of the quadrivalent human papillomavirus vaccine found that it is highly efficient in men aged from 16 to 26 years, with seroconversion within 7 months, with antibodies being detected even at 36 months, numbers comparable with those encountered in clinical trials conducted in female patients (51). In a study conducted by Giuliano et al (52) similar results regarding the efficacy of the quadrivalent HPV vaccine against HPV infection in male patients were found (53)(54)(55)(56)(57)(58)(59)(60)(61).…”
Section: Prevention Of Hpv Infection In Menmentioning
confidence: 71%
“…However, a study that focused on the immunogenicity of the quadrivalent human papillomavirus vaccine found that it is highly efficient in men aged from 16 to 26 years, with seroconversion within 7 months, with antibodies being detected even at 36 months, numbers comparable with those encountered in clinical trials conducted in female patients (51). In a study conducted by Giuliano et al (52) similar results regarding the efficacy of the quadrivalent HPV vaccine against HPV infection in male patients were found (53)(54)(55)(56)(57)(58)(59)(60)(61).…”
Section: Prevention Of Hpv Infection In Menmentioning
confidence: 71%
“…To a clear and precise final diagnosis, a thorough history and clinical features of lesions should be correlated with complex testing-histopathologic examination, DIF, IIF, cutaneous patch testing ( 20-22 ). Also, it is important to mention that the diagnostic process of OLP and OLL demands continuous follow-up and if necessary additional biopsies for histopathological evaluation and immunofluorescence tests ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…While there are numerous publications regarding RCM imaging of various skin conditions ranging from tumors to infections and inflammatory conditions [33][34][35][43][44][45][46][47], there are only a few reports in the literature related to the non-invasive diagnosis of lip lesions. Whilst RCM knowledge and experience in the field of non-melanoma skin cancer is constantly expanding [48][49][50][51], obtaining biopsies is still an invasive procedure with its own limitations, mainly due to cosmetic reasons and the risk of sampling errors.…”
Section: Discussionmentioning
confidence: 99%